Layanan Konseling Individual Pada Pasien HIV AIDS (Studi Kasus di RSJD Sungai Bangkong Provinsi Kal-Bar) - Pilga Ayong Sari; Adiansyah Adiansyah; Lini Larasati (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2022)
Every human being craves happiness. But happiness is not that easy to feel for people who are infected with the HIV AIDS virus. Not infrequently they feel mental pressure and stigma of society that is not good so that feeling defresi even leads to suicide. Efforts that can be done in the framework of mental recovery of HIV AIDS patients are through individual counseling. In the process of individual counseling of HIV aids patients can be done through four stages. The fundamental reason for this study was conducted was to dig up information related to individual counseling in HIV AIDS, especially in Bangkong River Hospital in West Kalimantan Province through a qualitatively derifriftive approach with case study methods. After receiving individual counseling services, most consors showed many positive changes by showing an open attitude and being able to accept their status as an ODHA. Konseli is also no longer minder to get along in the midst of society. In fact, some people also feel as if they have new hopes and life goals such as being small businesses such as trading fried foods or selling gravy.